Avaliação da abundância, atividade e representatividade das larvas de insetos na fauna do solo na área do experimento Esecaflor, na Estação Cientifica Ferreira Penna, Melgaço, Pa - Basante, Flávio Teixeira (Museu Paraense Emílio Goeldi, 2023)
The dynamics of nutrient cycling is responsible for maintaining ecosystems established on soils of low fertility, often found in the Amazon. Insect larvae contribute to soil structure and mechanical breakdown of organic tissues in the burlap. Microclimatic changes can act on these populations, influencing the abundance and distribution of individuals. This work aims to contribute to the identification and determination of the representativeness of insect larvae in the soil arthropod fauna, emphasizing the order Diptera, during the periods before and after the installation of the Esecaflor experiment, in the Scientific Station Ferreira Pena, Melgaço/PA, which consists of an induced drought, blocking 80% of the rainwater that falls on the soil. Two plots were established in the area, one for the experiment and the other a control plot. Larvae captured in Pitfall traps and Winckler's Extractors were analyzed, coming from four campaigns, in June and November 2001 (pre-water exclusion period) and in April and June 2002 (water exclusion). We found that, on average, insect larvae represented 1.61 % of the total arthropod fauna captured in the control and experimental plots. Only the orders Coleoptera and Diptera were collected in all campaigns in both plots. When comparing the results of collections made at the same period of the year (June 2001 and 2002), it was observed that Diptera larvae showed a significant decrease in abundance in the experimental plot in relation to the control. In view of the results presented, there was no significant variation in the response of coleoptera larvae to the experimental effect. The design used did not prove to be completely adequate to estimate the effects of water exclusion on soil macrofauna larvae. For a better analysis, it is intended to increase the number of plots, using a gradient in soil moisture content.